2020
DOI: 10.1021/acsapm.9b01151
|View full text |Cite
|
Sign up to set email alerts
|

Humidity-Driven Transparent Holographic Free-Standing Polyelectrolyte Films

Abstract: In the present work, transparent holographic poly­(diallyldimethylammonium chloride) (PDADMAC)/heparin and PDADMAC/poly­(styrenesulfonate) (PSS) films were synthesized via polyelectrolyte coacervates. PDADMAC/heparin films were obtained without temperature treatment. Thin holographic free-standing films with a 1 μm grating period and uniform surface of a polyelectrolyte complex were readily and quickly made by pressing polyelectrolyte coacervate, the hydrated viscoelastic fluid-like form of polyelectrolyte com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Aqueous solutions of oppositely charged polyelectrolytes (PEs) phase separate upon mixing, leading to the formation of a dilute supernatant and a polymer-rich phase known as a polyelectrolyte complex (PEC). PECs are formed due to electrostatic attractions between oppositely charged PEs and the entropic release of counterions and water. PECs can exist as solid-like complexes or liquid-like coacervates, and the physical properties are affected by salt, temperature, water, pH, and hydrophobicity of the PEs. This leads to applications of PECs in drug delivery systems, humidity sensors, separation membranes, electrochemistry, and many more. However, there is little information regarding the impact of complexation pH and water content on the mechanical properties and relaxation of PECs.…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous solutions of oppositely charged polyelectrolytes (PEs) phase separate upon mixing, leading to the formation of a dilute supernatant and a polymer-rich phase known as a polyelectrolyte complex (PEC). PECs are formed due to electrostatic attractions between oppositely charged PEs and the entropic release of counterions and water. PECs can exist as solid-like complexes or liquid-like coacervates, and the physical properties are affected by salt, temperature, water, pH, and hydrophobicity of the PEs. This leads to applications of PECs in drug delivery systems, humidity sensors, separation membranes, electrochemistry, and many more. However, there is little information regarding the impact of complexation pH and water content on the mechanical properties and relaxation of PECs.…”
Section: Introductionmentioning
confidence: 99%
“… 31 35 Porous saloplastic materials are obtained by centrifugation 31 , 36 and electrospinning 37 of coacervate phases or by desalting a homogeneous PE solution in between semipermeable membranes. 38 In addition, doped PECs can be extruded to obtain dense materials in various shapes (tape, tube, rod, and fiber) 32 , 33 or spin-coated, 34 , 39 cast, 40 , 41 or pressed in between templates 42 , 43 to obtain transparent films. Moreover, some of the saloplastics show self-healing behavior which can operate under room temperature and tuned by type of salt.…”
Section: Introductionmentioning
confidence: 99%
“…One such example is a poly (diallyldimethylammonium chloride)/heparin film modified with cobalt chloride ( Figure 5 a). [ 70 ] Nikolaev et al. [ 70 ] showed that even in such a simple system, complex, competitive thermodynamically favorable molecular hydration reactions proceed.…”
Section: Freestanding Filmsmentioning
confidence: 99%
“…[ 70 ] Nikolaev et al. [ 70 ] showed that even in such a simple system, complex, competitive thermodynamically favorable molecular hydration reactions proceed. The incorporation of redox molecules, such as ferrocene, into the polystyrene sulfonic acid matrix, allows nitric oxide redox detection.…”
Section: Freestanding Filmsmentioning
confidence: 99%
See 1 more Smart Citation